Characterisation of Mineralised Material from the Loki’s Castle Hydrothermal Vent on the Mohn’s Ridge - Ben Snook; Kristian Drivenes; Gavyn K. Rollinson; Kurt Aasly (Minerals, 2018)
Loki’s Castle on the Arctic Mid-Ocean Ridge (AMOR) is an area of possible seafloor massive sulphide (SMS)-style mineralisation under Norwegian jurisdiction, which, due to mounting social pressure, may be a strategic future source of base and precious metals. The purpose of this study is to characterise mineralised material from a hydrothermal vent system on the AMOR in detail for the first time, and to discuss the suitability of methods used; reflected light microscopy, X-ray diffraction (XRD), whole rock geochemistry, electron probe micro-analysis (EPMA), and QEMSCAN. The primary sulphide phases, identifiable by microscopy, are pyrite and marcasite with minor pyrrhotite and galena, but multiple samples from the Loki’s Castle contain economically interesting quantities of copper (hosted in isocubanite and chalcopyrite) and zinc (hosted in sphalerite), as well as silver and gold. This reinforces the notion that slow spreading ridges may host significant base metal deposits. Micro-textures (chalcopyrite inclusions and exsolutions in sphalerite and isocubanite respectively) are typically undefinable by QEMSCAN, and require quantitative measurement by EPMA. QEMSCAN can be used to efficiently generate average grain size and mineral association data, as well as composition data, and is likely to be a powerful tool in assessing the effectiveness of SMS mineral processing.